Fluorescent electrospun PMMA microfiber mats with embedded NaYF4: Yb/Er upconverting nanoparticles. (23rd May 2019) - Antoniadou, Myrto; Pilch-Wrobel, Aleksandra; Riziotis, Christos; Bednarkiewicz, Artur; Tanasă, Eugenia; Krasia-Christoforou, Theodora
Abstract: Functional upconverting nanoparticles (UCNPs) can offer new possibilities in fluorescent applications as they exhibit desired characteristic properties like large shift between the fluorescent emission signal and the infrared excitation wavelength, multi- and narrow-band absorption and emission in visible and near infrared - Vis/NIR, together with excellent photostability and low toxicity as opposed to semiconducting quantum dots. The upconversion luminescence emission or quenching characteristics of UCNPs can be altered upon exposure to physical or chemical environmental factors providing thus a functionality that can be utilized for sensing or imaging. Furthermore their functionalization with suitable indicator dyes or recognition elements can extend the range of luminescence response and ratiometric sensing to specific analytes. Synergistically, electrospun nano- and microfibers offering large surface area can enhance the functionality of UCNPs by retaining the fluorescence efficiency and improving the overall responsivity due to dramatically increased surface. For the optimization of this hybrid material system the controllable incorporation of UCNPs is required especially at increased concentration conditions needed for high brightness. Herein, we report the fabrication, morphological and optical characterization of electrospun polymer-based nanocomposite fibers, consisting of poly(methyl methacrylate) (PMMA) and upconverting lanthanide doped nanoparticles of the type NaYF4 : 20% Yb 3+ /2% Er 3+ @ NaYF4 . Morphological studies regarding the uniformity and aggregation effects of the UCNP inclusion within the fibers have been implemented followed by upconversion emission characterization by pulsed near-infrared excitation. The study and optimization of such nanocomposite fibrous systems could provide useful insights for the development of efficient upconverting electrospun fiber mats for a number of imaging and sensing applications.